Modelagem matemática nas aulas de cálculo: uma estratégia que pode contribuir com a aprendizagem dos alunos de engenharia - ARAÚJO, Alyne Maria Rosa de (Universidade Federal do Pará, 2012)
This work objects to analyze the possible efects which the use of Mathematics Modelling, while the teach strategy provoke in students’ learning process of subject Calculation III – DOE (Differential Ordinary Equations). The research was develop in a students’ classroom of second year of Computing Engineer course, at Federal University of Pará. The work is qualitative where they were took into consideration the social aspects that were in a university classroom. Important to point out there was direct participation of teacher-researcher of Mathematics. For that I could do data collect I used some instruments that I considered essential, such as, observations, recordings in video, semi-structures questionnaires and registers wrote of students. Of possession some preliminary results it was possible for me to watch as to Mathematics Modelling develops a relevant paper in the learning of contents Mathematics for the part of students. Cause it was possible they interected with others areas of knowledge it being this way encourage to realise research and simultaneously was part of process of teach and learning was made in the classroom. I also observed the Mathematics Modelling as strategy of teaching and learning; it led the students to arouse to reflexive aspects and critics asleep for learning with quality and agreed way they built your academic knowledges and profissionals.